Perspektif Wesleyan-Arminian terhadap Konsep Dikuduskan karena Posisi dan Implementasinya dalam Kehidupan Orang Percaya - Yupiter Hulu (Sekolah Tinggi Theologia Nazarene Indonesia, 2016)
In the mid of the world bustle, civilization and technology development, many Christian are ignoring the Biblical holiness standards. Apparently, enthusiasm in discussing, learning and understanding about holiness values and standards is very less. Some people think that it is too hard to be achieved and experienced. God calls His people to be a holy and pleasing in His sight. In New Testament Understanding when God calls His people, He will not let them walk alone. The works of God through the Holy Spirit will help and equip believers to live their life. Through the gift of the Holy Spirit, believers equipped and given a new “position” that might believers grow in it and please God through their new identity.